Situation Report: Romania, 19 August 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to Middle East Truce Developments in Romanian Higher Education Institutes Restrictions on Travel Abroad More Party Contacts Reorganization of the State Committee on Culture and the Arts International Apiculture Institute Established in Romania